2012
DOI: 10.1590/s0365-05962012000200022
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy findings in tinea capitis: case report and literature review

Abstract: Dermoscopy is a method of increasing importance in the diagnoses of cutaneous diseases. On the scalp, dermoscopic aspects have been described in psoriasis, lichen planus, seborrheic dermatitis and discoid lupus. We describe the "comma" and "corkscrew hair" dermoscopic aspects found in a child of skin type 4, with tinea capitis. Keywords: Child; Dermoscopy; Tinea capitis Resumo: A dermatoscopia é um método que ganha cada vez mais importância na diagnose de diversas dermatoses. No couro cabeludo, já foram descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 4 publications
3
26
0
1
Order By: Relevance
“…In TTM, proximal hair residues of different lengths are present in every field of view (19). A summary of the key features, which allow us to distinguish between TTM and AA in trichoscopy, are shown in Table SIII 1 . Our findings in tinea capitis included comma hairs, which are a trichoscopic hallmark of the disease (33)(34)(35)(36). Comma hairs seem to be specifically associated with dermatophyte-induced fungal scalp infections.…”
Section: Discussionmentioning
confidence: 55%
“…In TTM, proximal hair residues of different lengths are present in every field of view (19). A summary of the key features, which allow us to distinguish between TTM and AA in trichoscopy, are shown in Table SIII 1 . Our findings in tinea capitis included comma hairs, which are a trichoscopic hallmark of the disease (33)(34)(35)(36). Comma hairs seem to be specifically associated with dermatophyte-induced fungal scalp infections.…”
Section: Discussionmentioning
confidence: 55%
“…In tinea capitis fractured and slightly curved hair shafts, that resemble a comma at dermoscopic examination, zig-zag-hairs and corkscrew hairs (in patients of African descent) are characteristic feature of dermatophyte infection. 3,4,5 Furthermore in a recent case report the authors showed that hair trichoscopy features of tinea capitis in a patient disappeared with successful therapy and hair regrowth. 13 In veterinary dermatology, screening tests for dermatophytosis include Wood's-lamp examination and direct microscopic examination of the fluorescent hairs.…”
Section: Discussionmentioning
confidence: 99%
“…2 For example, although microscopic examination of infected hairs and fungal culture are considered the gold standard for diagnosis of tinea capitis in humans, dermoscopy of hair has been demonstrated to assist in the initial clinical diagnosis. 3 Indeed, slightly curved, fractured hair shafts, that resemble a comma at dermoscopic examination have been reported as a characteristic feature of both endothrix and ectothrix tinea capitis due to Microsporum canis and Trichopyton tonsurans infection.…”
Section: Introductionmentioning
confidence: 99%
“…Pediculosis capitis is a parasitic disease caused by an ectoparasite – the head louse. It is epidemic and involves intense pruritus and secondary skin lesions [25]. The therapeutic process of pediculosis capitis consists in several elements: topical treatment involving mechanical removal of nits, general treatment, prophylaxis and monitoring the patients’ surroundings [26, 27].…”
Section: Psychic Disturbances Concerning the Hairmentioning
confidence: 99%